Modulation of Connexin-36 Gap Junction Channels by Intracellular pH and Magnesium Ions - Rimkute, Lina; Kraujalis, Tadas; Snipas, Mindaugas; Palacios-Prado, Nicolas; Jotautis, Vaidas; Skeberdis, Vytenis A.; Bukauskas, Feliksas F. (Frontiers in Physiology, 2018)
Connexin-36 (Cx36) protein forms gap junction (GJ) channels in pancreatic beta cells and is also the main Cx isoform forming electrical synapses in the adult mammalian brain. Cx36 GJs can be regulated by intracellular pH (pHi) and cytosolic magnesium ion concentration ([Mg2+]i), which can vary significantly under various physiological and pathological conditions. However, the combined effect and relationship of these two factors over Cx36-dependent coupling have not been previously studied in detail. Our experimental results in HeLa cells expressing Cx36 show that changes in both pHi and [Mg2+]i affect junctional conductance (gj) in an interdependent manner; in other words, intracellular acidification cause increase or decay in gj depending on whether [Mg2+]i is high or low, respectively, and intracellular alkalization cause reduction in gj independently of [Mg2+]i. Our experimental and modelling data support the hypothesis that Cx36 GJ channels contain two separate gating mechanisms, and both are differentially sensitive to changes in pHi and [Mg2+]i. Using recombinant Cx36 we found that two glutamate residues in the N-terminus could be partly responsible for the observed interrelated effect of pHi and [Mg2+]i. Single mutations of glutamate at positions 8 and 12 attenuated the stimulatory effect of intracellular acidification at high [Mg2+]i and double mutation reversed stimulatory effect to inhibition. Moreover, Cx36*E8Q lost the initial increase of gj at low [Mg2+]i and double mutation lost the sensitivity to high [Mg2+]i. These results suggest that E8 and E12 are involved in regulation of Cx36 GJ channels by Mg2+ and H+ ions.